The Use of Blog to Enhance Students’ Writing Motivation - Sahrun Sudirman; Sarmina Ati (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2019)
The low of undergraduate students’ writing motivation is one of the classic problems encountered in many universities around the world. This phenomenon can be observed from the frequency of text produced by university students in various levels. Teachers around the world had practiced many methods and strategies in hope that the students’ writing motivation could be enhanced. However, this classic problem is still faced in the classroom today. It is interesting that the students who seldom to write in the classroom but are very active in writing in social media. The researcher then decided to investigate whether blog can enhance the students’ writing motivation. 21 students were involved in this research. After observing the students’ blog in almost 5 months and gathering information through open questionnaires, it has been concluded that blog could enhance the students’ writing motivation but the lack of students’ knowledge on how to operate the blog could be the reason why the students’ writing motivation (in this research) enhancement occurred only in small degree.